Elastic and Optoelectronic Properties of KCdF3： ab initio Calculations through LDA/GGA/TB-mBJ within FP-LAPW Method - K. Ephraim Babu N. Murali K. Vijaya Babu B. Kishore Babu V. Veeraiah (中国物理快报：英文版, 2015)
Ab initio calculations are performed on the electronic, structural, elastic and optical properties of the cubic per- ovskite KCdF3. Tile Kohn Sham equations are solved by applying the full potential linearized augmented plane wave （FP-LAPW） method. The exchange correlation effects are included through the local density approximation （LDA ）, generalized gradient approximation （GGA） and modified Becke-Johnson （mBJ） exchange potential The calculated lattice constant is in good agreement with the experimental result. The elastic properties such as elastic constants, anisotropy factor, shear modulus, Young＇s modulus and Poisson＇s ratio are calculated. KCdF3 is ductile and elastically anisotropic. The calculations of the electronic band structure, density of states （DOS） and charge density show that this compound has an indirect energy band gap （M-F） with a mixed ionic and covalent bonding. The contribution of the different bands is analyzed from the total and partial density of states curves. Optical response of the dielectric functions, optical reflectivity, absorption coefficient, real part of optical conductivity, refractive index, extinction coefficient and electron energy loss, are presented for the energy range of O-40eV. The compound KCdF3 can be used for high-frequency optical and optoelectronic devices.